2020
DOI: 10.1371/journal.pone.0233997
|View full text |Cite
|
Sign up to set email alerts
|

Where is your field going? A machine learning approach to study the relative motion of the domains of physics

Abstract: We propose an original approach to describe the scientific progress in a quantitative way. Using innovative Machine Learning techniques we create a vector representation for the PACS codes and we use them to represent the relative movements of the various domains of Physics in a multi-dimensional space. This methodology unveils about 25 years of scientific trends, enables us to predict innovative couplings of fields, and illustrates how Nobel Prize papers and APS milestones drive the future convergence of prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The classification scheme provided by the PACS code has certain limitations as well. Given the availability of large scale data sets, such as Microsoft Academic Graph (Wang et al, 2020) and advances in machine learning tools to identify and classify topics from papers (Qian et al, 2020;Chinazzi et al, 2019;Palmucci et al, 2020;Shen et al, 2019), it would be important to check if similar patterns can be observed in other data set. Finally, we adopt the whole counting in this study that gives equal credit to all co-authors.…”
Section: Discussionmentioning
confidence: 99%
“…The classification scheme provided by the PACS code has certain limitations as well. Given the availability of large scale data sets, such as Microsoft Academic Graph (Wang et al, 2020) and advances in machine learning tools to identify and classify topics from papers (Qian et al, 2020;Chinazzi et al, 2019;Palmucci et al, 2020;Shen et al, 2019), it would be important to check if similar patterns can be observed in other data set. Finally, we adopt the whole counting in this study that gives equal credit to all co-authors.…”
Section: Discussionmentioning
confidence: 99%
“…In an even more recent work, Palmucci et al . [ 25 ] propose a framework for describing the time evolution of scientific fields, allowing the authors to make predictions about their relative dynamics. The authors use records from the American Physics Society data on articles published during a given period to learn embeddings for PACS codes, which are numerical identifiers used as tags to categorize papers according to physics subfields.…”
Section: Related Workmentioning
confidence: 99%
“…It has been mostly used for the purpose of information retrieval and documents classification (which is the reason why it appears in the same group as LDA in Fig. 1), but can also be a useful tool to analyze science's evolution, mostly at the micro-level of terms-to-terms similarities (Palmucci et al 2019;Tshitoyan et al 2019;Tacchella et al 2020).…”
Section: Mapping Science and Knowledgementioning
confidence: 99%